Implementasi Model Pembelajaran Berbasis Proyek dalam Meningkatkan Keterampilan Berpikir Kritis Peserta Didik SMP Negeri 1 Dolok Batu Nanggar - Chesilia Panjaitan; Eduward Situmorang (Young Journal of Social Sciences and Humanities, 2026)
The development of 21st-century education requires students to possess critical thinking skills as a fundamental competency in facing academic and social challenges. However, learning practices at the junior high school level are still predominantly teacher-centered, limiting students’ opportunities to develop higher-order thinking skills. This study aims to examine the implementation of Project-Based Learning (PjBL) in improving the critical thinking skills of ninth-grade students at SMP Negeri 1 Dolok Batu Nanggar. This research employs a quantitative approach with a quasi-experimental design. The research subjects consisted of Grade IX students divided into experimental and control groups. Data were collected through critical thinking tests, classroom observations, and documentation. Data analysis was conducted using descriptive and inferential statistical techniques. The findings indicate that the implementation of Project-Based Learning significantly improves students’ critical thinking skills compared to conventional learning models. Therefore, Project-Based Learning can be considered an effective instructional model for enhancing critical thinking skills at the junior high school level